Karakteristik Mi Berbasis Ubi Jalar dengan Substitusi Pati Sagu atau Pati Ubi Banggai - Karsi Ambarwati; Elvira Syamsir; Sedarnawati Yasni (Jurnal Teknologi dan Industri Pangan, 2022)
Sweet potato is a local food that can be used to support food diversification programs. It can be used as a raw material to produce a diverse type of food products, for example noodles. The addition of sago starch and banggai starch to sweet potato noodle dough is to improve the quality of noodles because these two starches are more prone to retrograde. The purpose of this study was to determine the effect of starch type, extrusion temperature, and water addition on the sweet potato noodles’ quality. The types of starch added were sago starch and banggai starch, with extrusion temperature settings, which were 90 and 95°C, and the water additions were 40 and 35%. Analysis was carried out on the characterization of the flour and physical properties of sweet potato noodles. The best noodle processing conditions were with the addition of 15% sago starch, 95°C extrusion temperature, and 40% water added. This formula produced sweet potato noodles with low brightness, having redness and yellowish colour. It had a hardness value above 3000 g, with higher elasticity and elongation than the other formulas, and also had lower adhesiveness and cooking loss value.